2011
DOI: 10.2169/internalmedicine.50.4467
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction following Food-dependent Exercise-induced Anaphylaxis

Abstract: A 70-year-old man with a history of food-dependent exercise-induced anaphylaxis (FDEIA) since age 50 was admitted to the emergency department with chest pain and urticaria caused by FDEIA. Coronary angiography revealed total occlusion of the proximal left anterior descending coronary artery. After thrombus aspiration, a bare metal stent was placed into the culprit lesion, resulting in no residual stenosis. Urticaria disappeared on the second hospital day. This is the first reported case, to our knowledge, in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…There are many case reports regarding AMI as an in-hospital complication of patients treated for conditions, such as endocarditis [24,25], acute pancreatitis [26], rheumatoid arthritis [27], venous thromboembolism [28], diabetes mellitus [29], antiphospholipid syndrome [30], ovarian hyperstimulation syndrome [31], anorexia nervosa [32], anaphylaxis [33], and blunt chest trauma [34]. Among the 121 patients with somatic conditions in this study (n = 121), the most frequent diagnosis was gastrointestinal (25%), followed by urological (20%) and neurological (18%) diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are many case reports regarding AMI as an in-hospital complication of patients treated for conditions, such as endocarditis [24,25], acute pancreatitis [26], rheumatoid arthritis [27], venous thromboembolism [28], diabetes mellitus [29], antiphospholipid syndrome [30], ovarian hyperstimulation syndrome [31], anorexia nervosa [32], anaphylaxis [33], and blunt chest trauma [34]. Among the 121 patients with somatic conditions in this study (n = 121), the most frequent diagnosis was gastrointestinal (25%), followed by urological (20%) and neurological (18%) diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been claimed that at least 33-50% of patients with EIA suffer from FDEIA. Acute myocardial infarction may be a rare, but severe complication of FDEIA [13]. In FDEIA, allergic reactions are elicited only when a triggering cofactor, such as physical activity, is added after ingestion of the causative food.…”
Section: Food-dependent Exercise-induced Anaphylaxismentioning
confidence: 99%
“…Typical type I allergic symptoms such as pruritus, urticaria, and dyspnoea usually appear on the skin, mucous membranes, and the respiratory and gastrointestinal tracts. Acute myocardial infarction may be a rare, but severe complication of FDEIA [13]. FDEIA is potentially life-threatening, and cases of death have been ascribed to FDEIA [14,15].…”
Section: Food-dependent Exercise-induced Anaphylaxismentioning
confidence: 99%
“…However, to the best of our knowledge, it has never been reported that the hypercoagulable state seen in CU is associated with an increased risk of thrombosis. On the contrary, there are a number of reports of cardiovascular events (particularly myocardial infarction) occurring during episodes of acute urticaria [54][55][56][57]. Various pathomechanisms have been hypothesized to link urticaria and the cardiac events, including coagulation involvement, coronary artery spasm and/or atheromatous plaque erosion or rupture induced by inflammatory mediators.…”
Section: Clinical and Therapeutical Implicationsmentioning
confidence: 99%